Relationship Between Anemia and Systemic Inflammation in People Living With HIV and Tuberculosis: A Sub-Analysis of the CADIRIS Clinical Trial - Araújo-Pereira, Mariana; Barreto-Duarte, Beatriz; Arriaga, María B.; Musselwhite, Laura W.; Vinhaes, Caian L.; Belaunzaran-Zamudio, Pablo F.; Rupert, Adam; Montaner, Luis J.; Lederman, Michael M.; Sereti, Irini; Madero, Juan G. Sierra; Andrade, Bruno B. (Frontiers in Immunology, 2022)
People with HIV (PWH) are at increased risk of developing active tuberculosis (TB), and anemia is a common complication in both conditions. Anemia in TB participants has been linked to immune activation, levels of inflammatory biomarkers in blood, and risk for HIV disease progression and death. In this study we show that anemia was associated with a more pronounced inflammatory profile in HIV-TB coinfected persons in a cohort of 159 individuals with advanced HIV disease (CD4 count < 100 cells/µL) recruited as part of a randomized clinical trial (NCT00988780). A panel of plasma biomarkers was assessed on plasma obtained prior to antiretroviral therapy (ART) initiation. We performed a series of multidimensional analyses including clinical variables and concentrations of inflammatory biomarkers to profile systemic inflammation of PWH with and without anemia. We observed that TB participants presented with moderately lower levels of hemoglobin than non-TB participants. These participants also presented a higher Degree of Inflammatory Perturbation (DIP) score, related to increased levels of IFN-γ and TNF. The DIP was associated with TB coinfection and anemia before ART initiation. Future mechanistic studies are warranted to assess the determinants of such associations and the implications on treatment outcomes.